The Influence of Policy on School Nursing Practice - Chamoff, Mae (My University, 2024)
Introduction/Significance: School nurses are in an optimal position to influence the health of a large population of school-age children. Literature suggests that school nursing practice varies greatly, and school nurse interventions are often focused on various priorities of school health. Policy implementation in schools that include school nurse intervention may facilitate an increase in specific school nurse practice. This case study examined the school nurse practice and school policy dyad of one school nurse in a rural area of North Carolina. Methods: Case study design was used to examine the practice of a unique case of a school nurse in a rural area of North Carolina and associated school policy. Secondary data generated from a de-identified school nurse interview was the primary source of evidence. Two additional sources of evidence were used, the school health website for the school district and the school’s policy related to school nutrition. The data were analyzed to identify similarities between the school nurse’s practice and related school policy. Results: One overarching theme was identified, 1) Inclusion of the school nurse in policy facilitated school nurse practice, and one subtheme was identified 1) Communication, school nurse awareness of existing policy and communication is vital. Findings indicated that the school nurse’s practice in this case was directly influenced by the presence of a related school policy and the school nurse's awareness of the policy. Both the school health website and the school policy reviewed integrated the role of the school nurse. Discussion: While the findings of this case study are not generalizable to all school nurses, findings support the impact on practice with the inclusion of the school nurse in policy and the school nurse's awareness of school policy.
Keywords: School nurse; policy; influence